Knowledge translation mechanisms in open innovation: the role of design in R&D projects. Issue 6 (9th October 2017) - Simeone, Luca; Secundo, Giustina; Schiuma, Giovanni
Abstract : Purpose: This paper aims to investigate the role of design as a knowledge translation mechanism in R&D-oriented open innovation. In particular, the paper intends to look at how design can be used as a means of knowledge transfer among various stakeholders who speak different languages and have divergent needs and interests in a process where knowledge openly flew across the boundaries of a high number of organizations. Design/methodology/approach: The paper combines the insights from theory with the empirical evidences gathered by adopting an extreme case study approach: the detailed analysis of a case study related to an R&D project funded by the European Commission and aimed to investigate and produce innovative serious games in the area of healthcare. The project gathered a large number of stakeholders and deliberately adopted design to support an open innovation approach. Findings: The paper provides insights into the use of design outputs such as artifacts, sketches, visual representations or prototypes to translate ideas, theoretical and technical requirements, documents and outputs into formats that can be more easily understood and appreciated by various stakeholders. This supports and favors coordination in open innovation projects where many different stakeholders are engaged in. Research limitations/implications: Although the adoption of an extreme case study approach offers important implications to understand the role of design in R&D-oriented open innovation, the use of a single case study represents the basis both to explore hypothesis and to provide first evidences that need to be further tested with other qualitative and quantitative analysis. Practical implications: The paper offers practical implications about how design can help individuals and organizations involved in R&D activities to better communicate and share knowledge among various stakeholders by aligning their different needs, interests and languages along the various phases of their project development. Originality/value: The originality of the paper lays at the intersection of three different fields: open innovation, knowledge management and design for innovation, thus integrating mature, but so far isolated, research streams. It provides insights for theory building by explaining the use of design as knowledge translational mechanism as well as it informs the practice by highlighting the power of design as a mean to support knowledge flows into open innovation-based R&D projects.